Memandiri Usahawan Berstatus Asnaf Melalui Model MLC - Abd Halim, Mohammad Naim; Maamor, Selamah; Osman, Amirul Faiz; Aziz, Ahmad Bashir @ Zolmat; Ahmad, Nor Hayati (Lembaga Zakat Negeri Kedah, 2022)
For a long time, Kedah State Zakat Board (LZNK) has played their role in helping to manage the distribution to asnaf throughout the state of Kedah. The main focus of LZNK trying to help is those who want and are learning and this effort coincides with the basic need of a person to 'self-sufficient' is nothing but knowledge. However, what is the knowledge and how is the knowledge to be adapted in the daily life of an asnaf or the asnaf's child so that he is able to be independent and eventually is removed from the list of asnafs and instead becomes a zakat payer. Thus, this study offers a program that adapts the ‘Mindset, Leadership and Competencies (MLC)’ Model to establish asnaf and focus on asnaf with entrepreneurial status. The results of this study found that this MLC Model has left effective implications in establishing the target asnaf group. The relatively significant effects before and after this MLC model was introduced to these entrepreneurial status asnaf are; i) has shown a significant change in the ‘mindset’ of asnaf from low to medium and high levels; and ii) changes to ‘business competencies’. The business competencies of these asnafs were originally at a medium level and have been successfully transformed to a high and very high level. As a result, the asnaf have managed to master the latest business knowledge and even be able to make social media a more effective marketing method, cheaper and reach a wide network of customers. MLC's approach becomes important not only to focus on the material element (business competence) alone but also to sustain entrepreneurs and prevent them from getting stuck towards disappointment, fear of loss and various negative things in the business that will be faced in the future